The circular economy model as a promising path towards regional ecological and economic balance - M. Yu. Dyakov (Управление)
The article presents the results of an analysis of the possibilities for the transition of the region’s economy to a circular economic model. According to the aim of this article the main economic activities and tools for making such a transition in Kamchatka Territory have been identified. The principles of the circular economy and its advantages over the traditional “linear” model have been analysed. On the example of the Kamchatka Territory, the preconditions and prospects for the region’s transition to a circular economy model in terms of the existing structure of production of goods and services have been analysed. Using MS Excel tools, the structure of the gross regional product has been analysed, according to the results of which the main economic activities that are promising for the transition to a circular model have been identified. Regional indicators for waste recycling and neutralisation have been analysed, and chain coefficients have been calculated for growth in the share of recycled and neutralised waste for Russia as a whole, for the Far Eastern Federal District and Kamchatka Territory. Based on the results of the calculation, it has been concluded that the coefficient values for the Kamchatka Territory lag behind those for the whole of Russia and the Far Eastern Federal District. A number of financial and economic, technological, legal and informational tools have been identified, the use of which makes it possible to implement the transition to a circular economic model. Fisheries, energy, tourism, recycling and waste management have been identified as the most promising economic activities for such a transition. The findings conclude that it is important to continue research into the various aspects of the transition to a circular economy, as well as continued coordinated efforts are needed to implement it.